2012
DOI: 10.1007/jhep04(2012)065
|View full text |Cite
|
Sign up to set email alerts
|

Multiplicities from black-hole formation in heavy-ion collisions

Abstract: The formation of trapped surfaces in the head-on collision of shock waves in conformal and non-conformal backgrounds is investigated. The backgrounds include all interesting confining and non-confining backgrounds that may be relevant for QCD. Several transverse profiles of the shocks are investigated including distributions that fall-off as powers or exponentials. Different ways of cutting-off the UV contributions (that are expected to be perturbative in QCD) are explored. Under some plausible simplifying ass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0
6

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 64 publications
(162 reference statements)
5
48
0
6
Order By: Relevance
“…Thermalization in the improved holographic background has been studied in [32] and it has been shown that without additional assumptions, such as an energy dependent cut-off at the high energy [28], one cannot reproduce the multiplicity dependence on energy observed at RHIC and LHC in this background. In [33] it has been noticed that the holographic realization of the experimental dependence of multiplicity on the energy [35] requires an unstable background.…”
Section: Introductionmentioning
confidence: 99%
“…Thermalization in the improved holographic background has been studied in [32] and it has been shown that without additional assumptions, such as an energy dependent cut-off at the high energy [28], one cannot reproduce the multiplicity dependence on energy observed at RHIC and LHC in this background. In [33] it has been noticed that the holographic realization of the experimental dependence of multiplicity on the energy [35] requires an unstable background.…”
Section: Introductionmentioning
confidence: 99%
“…This critical value depends on the energy of colliding particles and the value of a cosmological constant. The formation of TSs in head-on collisions of shock waves in gravitational theories with more complicated bulk dynamics, in particular, with the Einstein-dilaton dynamics, claimed to describe a holographic physics that is closer to QCD than the purely AdS theory [33,36,37], was recently considered by Kiritsis and Taliotis [38], 1 who found that the multiplicity increases as…”
Section: Jhep05(2012)117mentioning
confidence: 99%
“…It was proposed in [28] to solve this problem by removing a UV part of the AdS bulk. Shock waves corresponding to the BH with a nonzero dilaton field [36,37] were considered in [38], where it was shown that the lower bound on N ch scales is closer to s 1/4 N N .…”
Section: Jhep05(2012)117mentioning
confidence: 99%
See 1 more Smart Citation
“…The issue was studied by implementing various approaches in the literature. In [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] the collisions of gravitational shock waves are introduced to mimic the colliding nuclei in the relativistic collisions. In [24,25] time-dependent and boost-invariant metrics, associated with the plasma undergoing Bjorken expansion, were investigated and further generalized in [26] with a chemical potential.…”
Section: Introductionmentioning
confidence: 99%